Invincible - Palmer, Diana (Palmer, Diana. Long, tall Texans series., 2014)
When her photographic memory makes her the target of a criminal who will do anything to make her forget, Carlie Blair entrusts her life--and her heart--to a Lakota Sioux named Carson, a man she once despised.